SOCIO-ECONOMIC FACTORS INFLUENCING FEMALE STUDENTS’ RETENTION IN PUBLIC SECONDARY SCHOOLS IN MUKAA SUB-COUNTY, MAKUENI COUNTY, KENYA - Nzina, Jacinta W.; Mulwa, David M.; Kimiti, Richard (International Journal of Education and Research, 2019)
Socio- economic factors have been highlighted as of great importance in influencing the retention of female students in secondary schools globally. The purpose of this study was to establish the extent to which socio-economic factors influence female students’ retention in public secondary school in Mukaa Sub-county, Makueni County, Kenya. The study objectives were; to establish the influence of family financial status on female students, retention and to determine the influence of parent’s educational level on female students, retention. The study was guided by the Systems Theory of Management. The study employed descriptive survey research design. The target population of the study comprised of 37principals, 50 form four class teachers and 1,240 form four female students in public secondary schools in Mukaa Sub-county. Questionnaires and documentary analysis were used to collect the data. Descriptive statistics specifically percentage and frequency were used for analysis and data was presented in tables and graphs. From the study it was established that; family financial status influence female students’ retention to a great extent as indicated by 72.7% of the teachers and principals. Parents’ education level influence students’ retention to a great extent as indicated by 54.5% of the teachers and the principals. From the study, it was concluded that most female students drop out of school because of their parents’ poor financial status and high academic attainment of parents significantly reduces chances of secondary school dropout. This study recommends that: Government should review bursary policies for needy students and increase funding in secondary schools, communities should be empowered to alleviate poverty and enable families’ increase their income, Parents should be sensitized to fully understand the importance of completion of secondary education and school administrators should strengthen guidance and counseling department in secondary schools.
Keywords: Socio-economic factors; female students; retention